1998
DOI: 10.1136/fn.79.1.f21
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cerebral palsy in England and Scotland, 1984-9

Abstract: Aims-To report on the epidemiology of cerebral palsy in England and Scotland, to provide information on the prevalence of cerebral palsy and the severity of the disability or any co-morbidity. Methods-Cerebral palsy registers were compiled from multiple sources of ascertainment covering all of Scotland and the counties of Merseyside, Cheshire, Berkshire, Buckinghamshire, Northamptonshire and Oxfordshire in England. All cases of cerebral palsy born in 1984 to 1989, to mothers resident in the area, were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(79 citation statements)
references
References 8 publications
5
71
1
2
Order By: Relevance
“…Low gestational age is a well-known risk factor for CP. [28][29][30][31] We found that the combination of prematurity and infection to have a multiplicative effect on the risk of CP with a 20-fold increase in the risk of CP. This effect held true when we further stratified into very low gestational age infants.…”
Section: Discussionmentioning
confidence: 79%
“…Low gestational age is a well-known risk factor for CP. [28][29][30][31] We found that the combination of prematurity and infection to have a multiplicative effect on the risk of CP with a 20-fold increase in the risk of CP. This effect held true when we further stratified into very low gestational age infants.…”
Section: Discussionmentioning
confidence: 79%
“…14,16 Henceforth, the registers will be referred to as Mersey, North of England, Oxford, Northern Ireland, and Scotland, respectively. The geographic regions covered by these registers were for Mersey the counties of Cheshire and Merseyside; for the North of England the former health districts of Northumberland, Newcastle, and North Tyneside until 1990 and the former health Northern region after 1990; for Oxford the counties of Buckinghamshire, Berkshire, Northamptonshire, and Oxfordshire; and all of Northern Ireland and Scotland.…”
Section: Ukcpmentioning
confidence: 99%
“…The 5 participating registers were the Merseyside and Cheshire Cerebral Palsy Register 2,9,11 ; the North of England Collaborative Cerebral Palsy Survey 7,12 ; the Northern Ireland Cerebral Palsy Register 13 ; 4Child-the Four Counties Database of Cerebral Palsy, Vision Loss and Hearing Loss in Children 14,15 (formerly the Oxford Register of Early Childhood Impairments); and the Scottish Register of Children with a Motor Deficit of Central Origin. 14,16 Henceforth, the registers will be referred to as Mersey, North of England, Oxford, Northern Ireland, and Scotland, respectively.…”
Section: Ukcpmentioning
confidence: 99%
“…Indications for fetal heart rate monitoring in women receiving antenatal magnesium sulphate for neuroprotection should follow the fetal surveillance recommendations of the SOGC 2007 Fetal Health Surveillance: Antepartum and Intrapartum Consensus Guideline . (III-A) 11 . Since magnesium sulphate has the potential to alter the neonate's neurological evaluation, causing hypotonia or apnea, health care providers caring for the neonate should have an increased awareness of this effect .…”
mentioning
confidence: 99%